Non-invasive prenatal testing as a routine procedure of prenatal care: Perspectives and challenges regarding reproductive autonomy - Rubeis, Giovanni; Orzechowski, Marcin; Steger, Florian (Ethik in der Medizin, 2019)
In March 2019, the German Gemeinsamer Bundesausschuss (G‑BA; Federal Joint Committee) presented the result of the method assessment process on non-invasive prenatal testing (NIPT). The aim of this method assessment process was to decide whether NIPT should become a publicly funded procedure of routine prenatal care. The G‑BA decided in favor of NIPT, making the implementation of NIPT very likely, provided that other healthcare and political institutions also agree.
Gesehen am 05.12.2019